Some problems with macroeconometric modeling in the Caribbean - Samuel, Wendell A. (Institute of Social and Economic Research KingstonJM, 1986)
Considers efforts to incorporate desequilibrium in macro-modeling and discusses the integration of the money market adjustment mechanism into the other macro relationships. Examines the treatment of expectations in Caribbean macro-models and effects of data collection methods on disaggregation.